OrientasiEkonomi Islam dalam Arus Trend Ekonomi Era Global di Tengah Kegagalan Ekonomi Kapitalisme - Muwahid Shulhan (IAIN Ponorogo, 2012)
The convensional economic approach that was excessive to fulfill personal interest in Islamic countries has increased economic growth in the economy in western world. But behind this success,in fact they failed to actualize the social vision and normative purpose for creating economic science. In the next, it appeared a negative effect that was same as Fukuyama said “the Great Disruption”. For solving those dificulty problems faced by muslim countries must be started in making and realizing a Paradigm. A paradigm is a basic for answering all of the problems above. In that paradigm, there must be planted a new premis, in developing of the economic in Islamic rules and the literature of islamic economic building is based on the paradigm as in al-Qur’an and as-Sunah. al-Qur’an and al-Sunnah are the main point of our basic reference. The second premis of this methode refuses the imitative. The kapitalisme, socialisme and that derivation are not the ideal type, even we can collect another advantages sources for being adopted and integrated in islamic paradigm without reducing any rules.